A study to formulate microemulsion for application in near-wellbore treatment of sandstone formation - Ngo, Nguyen Van; Minh, Phan Van; Trung, Do Thanh; Công, Le Van (Petrovietnam Journal, 2013)
Near-wellbore treatment in the Bach Ho and Rong fields of Vietsovpetro has been facing more difficulties as these oil fields come to the later stage of operation. Contamination in near-wellbore zone has increased due to organic and inorganic deposition, oil/water emulsion and water blocking. In recent years, many oil and gas companies over the world have been studying and applying microemulsions based on oil, water, surfactants and additives for treatment of precipitation in near-wellbore zone, especially for treatment of organic deposition, oil-in-water emulsion and water blocking. In this study, a microemulsion system was formulated based on anionic surfactant, oil, water and cosolvent. The properties of the microemulsion were studied and evaluated for application in near-wellbore treatment and enhanced oil recovery.